External Evaluation of IMF Surveillance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
The IMF's surveillance over its member'seconomic policies is one of the institution's central activities. In keeping with the increasing transparency of the IMF; the Executive Board askes a group of independent external experts to evaluate IMF surveillance, to assess the effectiveness of such surveillance, and to make recommendations for improvements. The group's report looks at the methods, substance, and impact of surveillance, both on individual countries and on the global economy. This publication also includes the reactions of the Executive Board, management, and the staff to the external evaluation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet